The Youngest Korean Case of Urachal Carcinoma - Seung Ryeol Lee; Haeyoun Kang; Moon Hyung Kang; Young Dong Yu; Chang Il Choi; Kyung Hwa Choi; Dong Soo Park; Young Kwon Hong (Case Reports in Urology)
Urachal anomalies are relatively uncommon and result from incomplete obliteration of the urachus perinatally. In children, most urachal diseases including urachal cysts and sinuses are benign, and these can sometimes become secondarily infected. Malignant involvement of the urachus is rarely reported, one in 5 million people, accounting for 0.35% to 0.7% of all bladder cancers. There are only five cases of urachal cancer diagnosed at the age of twenties in English written literature. Age at the diagnosis of urachal carcinoma is important to understand pathogenetic transition from benign to malignancy. A 26-year-old man visited our clinic with gross hematuria starting a few months before. CT scan showed a 4.0 × 6.8 cm sized lobulated cystic mass over the bladder dome. Cystoscopy showed a ball-shaped extrinsic mass from the bladder dome with intact bladder mucosa. With an impression of urachal cancer, laparoscopic partial cystectomy with wide excision of urachus was performed. Final diagnosis was well differentiated mucinous urachal adenocarcinoma invading bladder muscle, staged as pT3a based on Sheldon’s staging system. To our best knowledge, this case is the youngest Korean case of urachal carcinoma (the fourth youngest ever in English written literature).